Reconstructive endovascular treatment of basilar artery fenestration aneurysms: A multi-centre experience and literature review. Issue 3 (June 2022) - Styczen, Hanna; Fischer, Sebastian; Gawlitza, Matthias; Meyer, Lukas; Goertz, Lukas; Maurer, Christoph; Alexandrou, Maria; Khanafer, Ali; Lobsien, Donald; Deuschl, Cornelius; Klisch, Joachim; Kabbasch, Christoph; et al.
Background: Data on outcome after endovascular treatment of basilar artery fenestration aneurysms (BAFAs) is limited. This study presents our multi-centre experience of BAFAs treated by different reconstructive techniques including coils, stent-assisted coiling (SAC), flow diversion and intra-saccular flow disruption with the Woven Endobridge (WEB). Methods: Retrospective analysis of 38 BAFAs treated endovascularly between 2003 and 2020. The primary endpoint was complete aneurysm obliteration defined as Raymond–Roy occlusion classification (RROC) I on immediate and follow-up (FU) angiography. The secondary endpoints were procedure-related complications, rate of re-treatment, and clinical outcome. Results: Endovascular treatment was feasible in 36/38 aneurysms (95%). The most frequent strategy was coiling (21/36, 58%), followed by SAC (7/36, 19%), WEB embolization (6/36, 17%) and flow diversion (2/36, 6%). A successful aneurysm occlusion (defined as RROC 1 and 2) on the final angiogram was achieved in 30/36 (83%) aneurysms including all patients presenting with baseline subarachnoid haemorrhage and 25/36 (69%) were occluded completely. Complete occlusion (RROC 1) was more frequently achieved in ruptured BAFAs (15/25, 60% v. 2/11, 18%; p  = 0.031). Procedure-related complications occurred in 3/36 (8%) aneurysms. Re-treatment was executed in 12/36 (33%) aneurysms. After a median angiography FU of 38 months, 30/31 (97%) BAFAs were occluded successfully and 25/31 (81%) showed complete occlusion. Conclusion: Reconstructive endovascular treatment of BAFAs is technically feasible with a good safety profile. Although in some cases re-treatment was necessary, a high rate of final aneurysm occlusion was achieved.